"A paradigm of possibility": Community mentors and teacher preparation. Issue 6 (September 2018) - Cipollone, Kristin; Zygmunt, Eva; Tancock, Susan
In this paper, we investigate mentor perspectives of their roles as de facto "teacher educators." Drawing upon three years of qualitative data, we argue that community voices and knowledge should be reflected in decisions regarding what and how children are taught. We assert that, by broadening the definition of "teacher educator" beyond university faculty to include community members, we create spaces through which the development of culturally responsive teaching can more authentically emerge. The larger study from which this paper is derived examines the innovative practices of a teacher preparation program at a Midwestern university in the United States of America, wherein majority White, female, middle-class candidates are paired with mentor families in a low-income African-American neighborhood. This program of cultural immersion builds relational ties between community members, and mentors facilitate candidates' movement beyond deficit perspectives of communities of color and simplistic notions of celebration to see cultural affirmation and contextual knowledge of children's lived experiences as critical to student success. In the present study, we challenge neoliberal "commonsense" in the preparation of teachers by privileging community voices and highlighting how mentors perceive their respective roles as teacher educators.